Teaching Grade Eight Science with Reference to the Science Curriculum - Rasel Babu (Intelektual Pustaka Media Utama, 2016)
A mixed methodological approach was used to explore to what extent the science curriculum was being reflected in science teaching-learning of grade VIII students in Bangladesh. 160 students were randomly selected and 10 science teachers were purposively selected as study respondents. Fifteen science lessons were observed. Data were collected via student questionnaires, teacher interviews, and classroom observation checklists. Grade VIII science teaching-learning activities were not conducted according to the instructions of the science curriculum. Most teachers did not adhere to the curriculum and teacher's guide. Teachers mainly depended on lecture methods for delivering lessons. Learning by doing, demonstrating experiments, scientific inquiry, rational thinking, and analysing cause-effect relationships were noticeably absent. Teachers reported huge workloads and a lack of ingredients as reasons for not practising these activities. Teachers did not use teaching aids properly. Science teaching-learning was fully classroom centred, and students were never involved in any creative activities.